A 3D MODELLING MENGGUNAKAN TINKERCARD UNTUK PEMBELAJARAN MATERI BANGUN RUANG SISI DATAR DITINJAU DARI PEMAHAMAN KONSEP MATEMATIKA PADA SISWA SMP - Nanang Khuzaini (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2021)
The purpose of this research is to produce 3D Modeling Tinkercard learning media for learning material of flat-sided building with good quality and suitable for use in mathematics learning. The quality criteria used refer to Nieveen's criteria, namely valid, practical, and effective. This type of research is development research. This study develops mathematics learning media using a development model adapted from Borg and Gall's development model. The development stages carried out are preliminary studies, planning, draft development, limited field trials, product revisions, small group trials, field trials, and distribution and use. The trials carried out include expert trials, small group trials, field trials. Field trials were carried out in class VIIIB SMP Negeri 2 Godean. The research instrument used was the material expert evaluation sheet, the media expert evaluation sheet, the student response sheet, and the evaluation test. This research produces 3D Tinkercard Modeling media for learning material quality and feasible flat-side building. The results of this study indicate that the learning media developed are valid, practical, and effective